Penerapan Akuntansi Lingkungan pada Industri Tempe Sanan Malang - Robiatus Salamah; Endah Susilowati (Ekonomis: Journal of Economics and Business, 2023)
The issue of environmental pollution continues to be everyone’s concern and arises as a result of the production process of a company or industry, so companies are expected to apply environmental accounting as a form of concern for the environment, which will provide benefits to users and society. Industries and companies are required to be able to protect their environment, not only to take advantage of it. The goal of this research is to discover how the use of environmental accounting serves as a form of effort in preventing waste pollution in the Tempe Industry Sanan Malang. The approaches and data collection techniques used in this study were a qualitative interpretive approach and direct interviews with the head of the waste management section and the accounting department related to the waste management costs incurred. The data used in this research comes from intervew documentation. The results of the study show that the Tempe Industry Sanan Malang has carried out its waste management well, as evidenced by the results of waste management in several innovative products to lift the economy of the surronding community as well as maintain business continuity in the midst of increasingly fierce competition. In addition, the Tempe Industry Sanan Malang has indirectly implemented environmental accounting, but not in its entirety. The industry has incurred costs related to waste management, such as the cost of recycling waste, the cost of purchasing the epidermis, the cost of milling, labor costs, etc. But there is still no separate bokkeeping; the industry sometimes only records the cost incurred, and only in a simple way. With this researc, it is hoped that the Tempe Industry Sanan Malang will implement environmental accounting even better.